The American Public's Attention to Politics in Conflict and Crisis, 1880-1963. - Urbatsch, Robert (Journal of Interdisciplinary History)
The article explores the history of public attitudes towards politics in the U.S. through an analysis of the naming of babies for presidents and presidential candidates between 1880 and 1963. Emphasis is given to topics such as presidential candidates in mass media, the impact of electoral success on naming, and public reaction to the massacre at Wounded Knee, South Dakota in 1890.